Analisis Beberapa Faktor Risiko Perdarahan Pasca Persalinan Di RSUD K.R.M.T. Wongsonegoro Kota Semarang - Purnamasari, Intan; Handaria, Diana; Anggraheny, Hema Dewi (Andalas Obstetrics And Gynecology Journal, 2024)
Background: Postpartum haemorrhage is cumulative blood loss more than 1,000 ml after cesarean section or more than 500 ml after the fetus is born vaginally after the 3rd stage of labor is completed accompanied by signs of hypovolemia. Based on data from the Directorate of Maternal Health in 2010-2013, the biggest cause of maternal death is bleeding.Methods: This study used a quantitative analytic observational approach to case control. The cases in this study were mothers who were diagnosed with postpartum hemorrhage in 2021. While the controls in this study were mothers who were not diagnosed with postpartum hemorrhage in 2021. The sample used consecutive sampling technique.Results: Total sample of 306 people, namely 153 cases and 153 controls. In the chi square test and logistic regression analysis, namely age (p=0.234, OR1=1.495), parity (p=0.005, OR1=2.233, OR2=2.261), pregnancy interval (p=0.034, OR1=1.760), labor induction (p=0.268, OR1=1.356), cesarean section (p=0.001, OR1=0.014), retained placenta (p=0.001, OR1=15.457, OR2=7.245), and preeclampsia (p=0.012, OR1=0.329) .Conclusion: There is a relationship between parity, gestational spacing, cesarean section, retained placenta, and preeclampsia with postpartum hemorrhage. Variable retained placenta has the highest risk for postpartum hemorrhage, continued parity, preeclampsia, and cesarean section. Caesarean section and preeclampsia variables are protective factors.